Day-to-day stationary link flow pattern - Yang, Fan; Zhang, Ding (Transportation research. Part B: methodological, 2009)
Day-to-day traffic dynamics aim at modeling driver’s day-to-day learning and behavior adjustment process and providing insight on how the traffic flow pattern evolves over time. A number of continuous-time path flow dynamics have been proposed and studied in the literature whose stationary path flow pattern coincides with user equilibrium. However, the application prospects of these findings are limited by the fact that it might be difficult for transportation management centers to measure and monitor day-to-day dynamic path flow pattern. On the other hand, thanks to the fast development of Intelligent Transportation Systems (ITS), the day-to-day link flow pattern can be more easily monitored and analyzed. Thus, it is not only of theoretical interest but also with implement viability to explore equilibrium in the perspective of link flow dynamics. This paper carries on the study originated by [Zhang, D., Nagurney A., Wu, J., 2001. On the equivalence between stationary link flow patterns and traffic network equilibria. Transportation Research, 35B, 731–748] in investigating the relationship between a stationary link flow (SLF) pattern and traffic equilibrium, and makes significant developments on the subject in the sense that we prove that five existing route choice adjustment processes in the literature are all special cases of a so-called rational behavior adjustment process (RBAP) and thus this RBAP is mild and reasonable and can serve as a general framework of modeling driver’s rational behavior.